Crystal structure of the retinoblastoma protein N domain provides insight into tumor suppression, ligand interaction, and holoprotein architecture. - Hassler, M; Singh, S; Yue, W; Luczynski, M; Lakbir, R; Sanchez-Sanchez, F; Bader, T; Pearl, L; Mittnacht, S (2007)
The retinoblastoma susceptibility protein, Rb, has a key role in regulating cell-cycle progression via interactions involving the central "pocket" and C-terminal regions. While the N-terminal domain of Rb is dispensable for this function, it is nonetheless strongly conserved and harbors missense mutations found in hereditary retinoblastoma, indicating that disruption of its function is oncogenic. The crystal structure of the Rb N-terminal domain (RbN), reveals a globular entity formed by two rigidly connected cyclin-like folds. The similarity of RbN to the A and B boxes of the Rb pocket domain suggests that Rb evolved through domain duplication. Structural and functional analysis provides insight into oncogenicity of mutations in RbN and identifies a unique phosphorylation-regulated site of protein interaction. Additionally, this analysis suggests a coherent conformation for the Rb holoprotein in which RbN and pocket domains directly interact, and which can be modulated through ligand binding and possibly Rb phosphorylation.